2022
DOI: 10.1002/lio2.861
|View full text |Cite
|
Sign up to set email alerts
|

Possible clinical implications of the structural variations between the tympanic membrane quadrants

Abstract: Introduction Retraction pockets and marginal perforations of the pars tensa of the tympanic membrane (TM) are most commonly found at superior posterior quadrant (SPQ). The patulous Eustachian tube tends to manifest in the same quadrant. Variation in the structure of the TM may explain these observations. Material and Methods A line defined by the manubrium was used to divide the pars tensa into anterior and posterior portions. A transverse line centered on the umbo divides the pars tensa into superior and infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Further inconsistencies exist in the distribution of thickness values over the TM. Kassem et al (24) found the posterior superior quadrant to be significantly thinner than the other quadrants. Kuypers et al (8) state that the posterior region is thinner than the anterior region, but the thickness increases from inferior to superior.…”
Section: Discussionmentioning
confidence: 98%
“…Further inconsistencies exist in the distribution of thickness values over the TM. Kassem et al (24) found the posterior superior quadrant to be significantly thinner than the other quadrants. Kuypers et al (8) state that the posterior region is thinner than the anterior region, but the thickness increases from inferior to superior.…”
Section: Discussionmentioning
confidence: 98%